Optimal radial distribution system reconfiguration using fuzzy adaptation of evolutionary programming - Venkatesh, B (2003)
Optimal reconfiguration of Radial Distribution System (RDS) is done under the umbrella of Supervisory Control and Data Acquisition (SCADA) systems to achieve the best voltage profile and minimal kW losses amongst several objectives. This problem requires the determination of the best combination of feeders from each loop in the RDS to be switched out such that the resulting RDS gives the optimal performance in the chosen circumstance. The problem has a discontinuous solution space and certain problem variables assume discrete values of zero or one. This paper proposes a method that uses fuzzy adaptation of Evolutionary Programming (FEP) as a solution technique. FEP technique has been chosen as it is particularly suited while solving optimization problems with discontinuous solution space and when the global optimum is desired. Fuzzy adaptation of EP is necessitated while considering optimization of multiple objectives. The proposed method is tested on established RDS and results are presented. (C) 2003 Elsevier Ltd. All rights reserved.